树突状细胞的体外培养及其抗癌作用 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: Immunocompromised patients with malignant tumor always lack of strong anti-tumor immune response, because the antigenicity of tumor cells is weak, and antigen-presenting cell function is low, so that can not be effectively presenting tumor antigens to the lymphocytes. Terefore, how to effectively induce anti-tumor immune response is the key issue. Trough the study on establishing a method to culture dendritic cells (DC) in vitro and to observe the anti-lung cancer immunological effect induced by DC, we provided defnite experiment basis for the clinic application of vaccine based on DC. METHODS: Trough the experiment we get the soluble antigen polypeptide from lung cancer cells GLC-82 by 3 mol/L potassium chloride. DCs are cultured and obtained from peripheral blood mononuclear cell by GM-CSF, IL-4 and TNF-a. DCs are identifed by flow cytometer (FCM) and immunostaining. DCs modifed by lung cancer tumor soluble antigen (TSA) and staphylococcal enterotox in A (SEA), DCs modifed by TSA or DCs modifed by SEA or DCs modifed by nothing were cultivated together with T lymphocyte, and the obtained cells are named TSA-SEA-DCL or TSA-DCL or SEA-DCL or DCL as effector cells. The anti-tumor activity of every effector cells against target cells was assayed with MT method. Shape of DCs and effector cells, and the process of killing target cells were observed in microscope. RESULTS: Induced DCs expressed more CD1a, CD80 and HLA-DR, which had typical cell traits such as tree branch. The killing ratio of the TSA-SEA-DCL in vitro to GLC-82 is larger than TSA-DCL, SEA-DCL and DCL, also larger than to K562. When the effector cells cultivate with target cells, we can observe the CTL approach and gather to the cancer cell, induce it necrosis and apoptosis. CONCLUSION: Ripe DCs that have typical characteristic and phenotype could be induced successfully. High potency and relatively specifc antilung caner effect can be prepared in virtue of DC Bacterin Induced by lung caner TSA and SEA.